Analysis of Tourism Development: A Case of the Beach Tourism in Buton Tengah, Southeast Sulawesi Province - La Bonto, Ahmad Zulkivar; Rofiaty, Rofiaty; Susilowati, Christin (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This study analyzes the development of beach tourism in Buton Tengah, namely, Mutiara beach in Gumanano Village, Wantopi Beach in Wantopi Village, and Katembe Beach in Madongka Village. This study involved stakeholders of beach tourism in Buton Tengah as informants. They are representatives from the Tourism Department, Assembly at Buton Tengah regional, Village Heads, Communities and tourists of each tourist destination. This research is a type of qualitative research with a case study approach, and also data collection using direct interviews to the informant. The result of this study shows that the first, beach tourism in Buton Tengah is a type of natural tourism that have unique difference between one type of tour with another tour, in addition, there are also cultural and artificial tours. Second, beach tourism in Buton Tengah is currently managed by the local government and the local village government. Third, there is a miscommunication between stakeholders which causes the development of beach tourism in Buton Tengah to be less developed and lack competitive. Fourth, the lack of competitiveness strategies implemented by stakeholders. The last, the lack of stakeholders' knowledge regarding the development of competitive beach tourism.